THE ROLE OF SCHOOL PRINCIPALS IN IMPROVING THE QUALITY OF EDUCATION: A TRANSFORMATIONAL LEADERSHIP PERSPECTIVE - Lukmanul Hakim; Soni Samsu Rizal (CV. TOTUS TUUS, 2026)
This study explores school principals’ roles in improving education quality through transformational leadership. The main problems identified are principals’ low understanding of the principles of transformational leadership and limitations in training and resources to support its implementation. This study used a systematic literature review approach to collect data from reliable sources relevant to the topic. The results indicate that dimensions of transformational leadership, such as individualized influence, inspirational motivation, intellectual stimulation, individualized consideration, and contingent reward, significantly impact improving the quality of education in Indonesian schools. Furthermore, challenges such as inadequate training and limited resources were also identified. However, solutions such as more structured training, government support, and empowerment of school communities can help address these challenges. This research makes an essential contribution to developing educational policy and implementing transformational leadership in schools. It offers practical recommendations for principals to improve the quality of education continuously.